INNOVATIVE-INVESTMENT DEVELOPMENT OF AGRICULTURE IN THE CONDITIONS OF FORMATION OF THE EXPORT-ORIENTED ECONOMIC SECTOR: SYSTEM APPROACH - Marianna VASILCHENKO; Ivan SANDU (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Creating a highly productive export-oriented agricultural sector of the economy and increasing the efficiency of agricultural production in agriculture is possible on the basis of stimulating innovation and investment. The purpose of this study is to assess the impact of investment resources on the activation of innovative processes on the example of the livestock industry and to develop recommendations for increasing the innovation and investment activity of agriculture in the context of the formation of an export-oriented economy. The author’s paradigm of increasing innovation and investment activity in the agricultural sector of the economy is formed on the basis of the concept of NIS, diffusion of innovations, as well as theories of structural transformation of the economy. As a result of the analysis and evaluation of the innovation and investment development of agriculture, tendencies have been identified for increasing innovative activity and the imbalance between the existing innovative potential and the effectiveness of its use. Differentiation of regions by the level of provision with investments in fixed assets in agriculture was carried out, interregional differences were revealed. The developed author's methodology for assessing the level of innovation of the livestock industry in the Russian regions will allow us to formulate approaches to improving the structural investment policy. The practical significance of the results of the study is to develop a scheme for the development of organizational and economic support for increasing innovation activity in the context of the formation of an export-oriented agricultural sector of the economy.